TEACHER’S CORRECTION STRATEGIES ON STUDENTS’ ERRORS IN EFL SPEAKING CLASS - Leni Nuraeni; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2018)
This study is aimed at identifying the types of students’ errors made in EFL speaking class and what the kind of teacher’s correction This study used descriptive qualitative method and the informants of this research was the EFL students at second semester at the department of English education, Universitas Kuningan. Techniques of collecting data used in this study were observation, questionnaire, and interview. Ellis’s theory used to classify the teacher’s correction strategy used and Arias’s theory used to classify the students’ errors type in EFL speaking class. The findings showed that there are five types of errors that made by the students, they are pronunciation, grammatical, lexical, semantic, and pragmatic. Pronunciation error was the most frequent error made by the students. While, there were strategies used by the teacher in correcting students’ errors, they were recast, repetition, explicit correction, elicitation, and clarification request. Recast strategy was used by teacher as a frequent strategy.